Lutte Contre Le Tabagisme Et Les Maladies Non Transmissibles En Côte d’Ivoire - Joël-Henri Gilles, Aloko-N’guessan Kouadio (European Scientific Journal, ESJ, 2018)
WHO is in charge of the fight against smoking and its consequences in the world. This institution makes recommendations to its member states in order to help them contain the scourge of smoking. The present study therefore evaluates the level of integration of these various recommendations of the WHO in the context of the fight against smoking in Côte d’Ivoire. It starts from the observation that the fight against smoking in Ivory Coast has produced for several years mixed results. From a methodological point of view, the approach adopted in this study is essentially qualitative. It consisted of conducting semi-structured interviews, a quantitative thematic content analysis and a bibliographic synthesis. Through this approach, we have achieved results that highlight the inadequacy of the legal framework and tobacco control tools in Côte d’Ivoire and the weakness of financial resources allocated to the fight against smoking in this country.